2021
DOI: 10.5937/poljteh2103061c
|View full text |Cite
|
Sign up to set email alerts
|

Global mapper 15.0: A comparative software tool in the design of open channel drainage systems

Abstract: This research aimed at computing peak flow discharge using state-of-theart technology for watershed analysis to design a suitable open channel to minimize the effects of flood hazard during and after rainfall in an environment. A comprehensive topographical survey data obtained by Shuttle Radar Topographic Mission was employed in this study. The result of the survey shows that both the maximum and minimum elevation at 61.9 m and 51.1 m, respectively, and the mean slope of the area was 0.012. Watershed analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
0
1
0
Order By: Relevance
“…Legend : With Global Mapper, nine (09) subwatersheds (SBVs) that feed the Mbao backwater have been identified (Figure 4). Global Mapper also made it possible to have the physical characteristics these SBVs presented in the results section (Table 1) [13].…”
Section: Topographymentioning
confidence: 99%
“…Legend : With Global Mapper, nine (09) subwatersheds (SBVs) that feed the Mbao backwater have been identified (Figure 4). Global Mapper also made it possible to have the physical characteristics these SBVs presented in the results section (Table 1) [13].…”
Section: Topographymentioning
confidence: 99%
“…Gaurav Singh and Singh (2022) [17] in their study used the free Copernicus DEM 30 m opensource to determine the geomorphometric and topo-hydrological parameters of the Betwa River Basin. They concluded that the basin has a roughly elongated shape, less flow of water is available, relative relief is less, and a weak drain system.…”
Section: Previous Studiesmentioning
confidence: 99%